2004
DOI: 10.1104/pp.103.033399
|View full text |Cite
|
Sign up to set email alerts
|

Wounding Enhances Expression of AtSUC3, a Sucrose Transporter from Arabidopsis Sieve Elements and Sink Tissues

Abstract: The Arabidopsis AtSUC3 gene encodes a sucrose (Suc) transporter that differs in size and intron number from all other Arabidopsis Suc transport proteins. Each plant species analyzed so far possesses one transporter of this special type, and several functions have been discussed for these proteins, including the catalysis of transmembrane Suc transport, and also Suc sensing and regulation of other Suc transporters. Here, we show that the AtSUC3 protein is localized in the sieve elements of the Arabidopsis phloe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
178
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 175 publications
(191 citation statements)
references
References 48 publications
11
178
0
2
Order By: Relevance
“…Whereas no such domain has been reported previously in the literature, the promoter of a related Suc-H 1 symporter, AtSUC3p, driving the expression of a membrane protein-GFP fusion, was shown to express strongly in the root tip epidermis (Meyer et al, 2004). The failure to observe a root tip epidermal expression domain in earlier work with AtSUC2p could be due the fact that a shorter, 900-bp fragment of the promoter was employed (a 900-bp fragment from plasmid pEPS1; Stadler et al, 2005), in contrast to the 2,141-bp fragment used here.…”
Section: Mcitrine Expressed By the Sumcr Construct Accumulates In Thementioning
confidence: 78%
“…Whereas no such domain has been reported previously in the literature, the promoter of a related Suc-H 1 symporter, AtSUC3p, driving the expression of a membrane protein-GFP fusion, was shown to express strongly in the root tip epidermis (Meyer et al, 2004). The failure to observe a root tip epidermal expression domain in earlier work with AtSUC2p could be due the fact that a shorter, 900-bp fragment of the promoter was employed (a 900-bp fragment from plasmid pEPS1; Stadler et al, 2005), in contrast to the 2,141-bp fragment used here.…”
Section: Mcitrine Expressed By the Sumcr Construct Accumulates In Thementioning
confidence: 78%
“…However, subsequent studies have questioned this hypothesis by finding that null mutations in AtSUC3 have no obvious phenotype and that AtSUC3 protein has measurable biochemical activity (Meyer et al, 2000;Barth et al, 2003). Interestingly, the gene is expressed in many sink tissues and is strongly induced by wounding (Meyer et al, 2000(Meyer et al, , 2004. The only report characterizing a group 3 SUT in grasses showed that the rice OsSUT4 gene is expressed in all tissues examined, although at higher levels in sink leaves (Aoki et al, 2003).…”
Section: Group 3 4 and 5 Sut Family Membersmentioning
confidence: 98%
“…The direction of assimilate flow from the apoplast is dependent on the chemical gradient, which, because of the high sink strength, is directed toward GCs. Additionally, because of the lack of CCs, the sucrose transporters AtSUC2 and AtSUC3, which have been postulated to retrieve sucrose that is lost from the phloem along the transport pathway, are absent from RKs (37,38). Consequently, nSEs lack the ability to retrieve sucrose.…”
Section: Nses Are Formed De Novo In Rksmentioning
confidence: 99%